Calculus: Early Transcendentals (2nd Edition)

Published by Pearson
ISBN 10: 0321947347
ISBN 13: 978-0-32194-734-5

Chapter 3 - Derivatives - 3.3 Rules of Differentiation - 3.3 Exercises - Page 151: 30


$y' = 6s-2$

Work Step by Step

$y=\frac{12s^3-8s^2+12s}{4s}=3s^2-2s+3$ Using Power Rule: $y'=3(2)s^{2-1}-2(1)s^{1-1}+3(0)s^{0-1} = 6s-2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.